Istilah Pendidikan Islam dalam Al-Qur’an dan Implikasinya terhadap Manajemen Pendidikan - Rahman, Zaky Dhiaulhaq; Alkafi, Kurnia; Lughowi, Rifyal Ahmad; Uyuni, Yuyun Rohmatul (JoIEM (Journal of Islamic Education Management), 2025)
Education is essential in shaping human life, acting as a strategic instrument for fostering character and nurturing individual potential. This research aims to obtain a complete and comprehensive concept of education regarding the actual education that Allah regulates in Islam and is contained in the verses of the Al-Quran that the author chose. In the realm of Islamic education, the emphasis goes beyond mere intellectual growth, highlighting the significance of moral integrity and spiritual depth. This article delves into the management of Islamic education, which includes various contexts such as formal, informal, and non-formal settings, including family education, pesantren (Islamic boarding schools), and majelis ta'lim (study circles). Effective management of Islamic education necessitates a thorough understanding and skill set to apply its principles successfully. Furthermore, this article discusses the vital role of the Qur'an and Hadith as foundational sources for Islamic education and management, stressing the importance of ongoing interpretation to adapt to the evolving times and circumstances.